2017
DOI: 10.1093/gerona/glx175
|View full text |Cite
|
Sign up to set email alerts
|

Negative Affect Is Associated With Higher Risk of Incident Cognitive Impairment in Nondepressed Postmenopausal Women

Abstract: We present the first evidence to date that greater NA, even in the absence of elevated depressive symptoms, is associated with higher risk of MCI and dementia. This suggests that NA may be an important, measureable and potentially modifiable risk factor for age-related cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Many studies have shown a relationship between cognitive errors and negative emotions, such as depression, and the cognitive behavioral therapy for treating negative emotions has also been recognized as effective [46,47,48]. In addition, the relationship between cognitive deficit and negative affect, such as depression, has been confirmed [49]. Patients with depression are unable to appropriately appreciate the future because they have rigid thoughts, which has been shown to affect emotional acceptance [48,50].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown a relationship between cognitive errors and negative emotions, such as depression, and the cognitive behavioral therapy for treating negative emotions has also been recognized as effective [46,47,48]. In addition, the relationship between cognitive deficit and negative affect, such as depression, has been confirmed [49]. Patients with depression are unable to appropriately appreciate the future because they have rigid thoughts, which has been shown to affect emotional acceptance [48,50].…”
Section: Discussionmentioning
confidence: 99%
“…Conscientiousness, in contrast, while not an emotional trait by definition, is associated consistently with lower negative affect, particularly less stress (Ebstrup, Eplov, Pisinger, & Jørgensen, 2011), lower stressor-related negative affect (Leger, Charles, Turiano, & Almeida, 2016), and faster recovery from stress (Javaras et al, 2012). Negative affect, in turn, increases dementia risk (Korthauer et al, 2018).…”
Section: Negative Affectmentioning
confidence: 99%
“…These studies are limited by their cross-sectional design or sole focus on Neuroticism. Parallel literatures have documented the predictive power of cognitive engagement (Wang, MacDonald, Dekhtyar, & Fratiglioni, 2017), negative affect (Korthauer et al, 2018), subjective health (Montlahuc et al, 2011), and social integration (Wilson, Krueger, et al, 2007) on cognitive outcomes. As described in the following, these potential mechanisms have been associated with personality and may be additional pathways that help explain the association with cognition.…”
mentioning
confidence: 99%
“…Life satisfaction predicted dementia in a sample of 1.751 elderly people without cognitive impairment at baseline who were followed for 5 years (adjusted OR = 0.70, CI = 0.51–0.96; Peitsch et al, 2016 ). This dementia risk is also related to negative affects according to a study conducted by Korthauer et al (2017) . The authors assessed affects in 2,137 elderly women without depressive symptoms who were followed for 11 years and concluded that negative affects were associated with greater cognitive decline, even when adjusting for the covariates of age, education, lifestyle, sociodemographic factors, global cognition, cardiovascular risk, and hormone therapy.…”
Section: Introductionmentioning
confidence: 95%